2022
DOI: 10.1021/acs.biochem.2c00064
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonate and α-Fluorophosphonate Analogues of d-Glucose 6-Phosphate as Active-Site Probes of 1l-myo-Inositol 1-Phosphate Synthase

Abstract: The biosynthesis of myo-inositol (mI) is central to the function of many organisms across all kingdoms of life. The first and rate-limiting step in this pathway is catalyzed by 1l-myo-inositol 1-phosphate synthase (mIPS), which converts d-glucose 6-phosphate (G6P) into 1l-myo-inositol 1-phosphate (mI1P). Extensive studies have shown that this reaction occurs through a stepwise NAD+-dependent redox aldol cyclization mechanism producing enantiomerically pure mI1P. Although the stereochemical nature of the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The MIPS regulates the biosynthesis of Ins and its derivatives such as phosphoinositide phosphates (PtdInsPs), Ins polyphosphates (IPs), and phospholipid phosphatidylinositol (PtdIns), which play important and varied roles in cell division, plant growth, organ development as well as biotic and abiotic stress responses [ 16 ]. This gene was reported for the first time in Archaeoglobus fulgidus and was observed to function at high temperatures [ 17 ]. Earlier studies have shown that three MIPS genes play important roles in Arabidopsis embryo development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MIPS regulates the biosynthesis of Ins and its derivatives such as phosphoinositide phosphates (PtdInsPs), Ins polyphosphates (IPs), and phospholipid phosphatidylinositol (PtdIns), which play important and varied roles in cell division, plant growth, organ development as well as biotic and abiotic stress responses [ 16 ]. This gene was reported for the first time in Archaeoglobus fulgidus and was observed to function at high temperatures [ 17 ]. Earlier studies have shown that three MIPS genes play important roles in Arabidopsis embryo development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%